An All‐Fabric Droplet‐Based Energy Harvester with Topology Optimization - Liang, Fei; Chao, Xujiang; Yu, Shudong; Gu, Yuheng; Zhang, Xiaohui; Wei, Xin; Fan, Jintu; Tao, Xiao‐ming; Shou, Dahua (Advanced energy materials, 2022)
The output power density of a triboelectric nanogenerator can be enhanced by several orders of magnitude by a field‐effect transistor like structure. However, the previously reported strip top electrode is not ideal for optimum generation and stable transfer of charges under practical dynamic conditions. Switched on by an impinged droplet, the bridged closed‐loop electric circuit transfers the accumulated charges by converting the conventional interfacial effect into a bulk effect. Randomly falling droplets cannot always exactly impinge the electrode with the desired spreading contact to achieve a high peak voltage, and a large fraction of low‐voltage direct‐contact and sliding‐contact modes will lead to low output and instability. To address this critical challenge, a topology‐optimized droplet energy harvesting fabric (TO‐DEHF) for stable and efficient output from randomly falling droplets is reported. The optimized fabric electrodes in a hexagonal network feature a stable open‐circuit voltage under moving and rotating patterns, threefold over that with the strip electrodes. The peak power density of the TO‐DEHF (71.8 mW m–2) is 4.8‐fold versus the latter (14.8 mW m–2). Moreover, the all‐fabric TO‐DEHF has high flexibility and breathability, based on which a self‐powered wireless wearable prototype is successfully demonstrated for detection of crucial droplet properties, including temperature, pH, and salinity. A novel topology‐optimized droplet energy harvesting fabric is rationally developed for stable and efficient output from randomly falling droplets. This all‐fabric droplet‐based energy harvester has high flexibility, durability, and breathability, based on which a self‐powered wireless wearable device can detect and monitor the crucial droplet properties, including temperature, pH, and salinity.